In Vivo and Cadaver Studies of the Canalicular/Lacrimal Sac Mucosal Folds. (8th May 2016) - You, Yongsheng; Cao, Jing; Zhang, Xiaogang; Wu, Wencan; Xiao, Tianlin; Tu, Yunhai
Abstract : Purpose. The study aimed to investigate canalicular/lacrimal sac mucosal folds (CLS-MFs) in vivo and in cadavers in order to explore their functional roles in the lacrimal drainage system. Method. The observations of CLS-MFs in vivo were performed on 16 patients with chronic dacryocystitis after undergoing an endonasal endoscopic dacryocystorhinostomy (EE-DCR). The lacrimal sacs and common canaliculi of 19 adult cadavers were dissected. The opening/closing of an orifice and mucosal fold was recorded. All of the specimens were subjected to a histological examination. Results. The upper and lower lacrimal canaliculi in all of the samples united to form a common canaliculus that opened to the lacrimal sac. CLS-MFs were observed in 10 of the 16 patients (62.5%) and 9 of the 19 cadavers (47.4%). The orifices or mucosal folds could be opened or closed when related muscles contracted or relaxed. Histological sections showed a mucosal fold at one side of an orifice. Conclusion. Common canaliculus is the most common type that the canaliculus opens to lacrimal sac. CLS-MFs exist in a certain ratio that can be opened/closed with the movement of the orifices. They may be involved in the drainage of tears or the pathogenesis of acute dacryocystitis or lacrimal sac mucocele.